ANALISIS PENGARUH LITERASI KEUANGAN, INKLUSI KEUANGAN, DAN PENGELOLAAN KEUANGAN TERHADAP KEPUTUSAN INVESTASI GENERASI Z DI KOTA KENDARI - Akbar Wahbi; Bakti; Wa Ode Harliyanti Unga; La Ode Ahmad Darwin; Ikbal (Halu Oleo University, 2024)
Generation Z is one of the groups of society with the largest number and workforce. Based on data from the Indonesia Stock Exchange (BEI), Southeast Sulawesi Province shows a positive trend in people investing. The number of investors will increase by 43.3% in 2022-2023 and the largest investors are those belonging to Generation Z. This is due to financial literacy and financial inclusion so that they are more aware of managing their finances to invest in safer and better places. This research uses a quantitative approach with a causal associative method. The number of respondents in the research was 97 respondents. The results in this study show that all variables (exogenous and endogenous) have a significant influence.